Nursing care in pain management in children with sickle cell anemia: na integrative review (Research, Society and Development, 2020)
Objective: to analyze the nursing care strategies employed in pain management in children with sickle cell anemia. Method: integrative literature review on the topic in the virtual databases Scielo, Lilacs, PubMed, MEDLINE and BDENF in the months of January and February. Results: 17 articles were selected and two analytical categories were identified: knowledge of professionals and education of children and family members about the pathological process of pain and pharmacological and non-pharmacological treatment for pain management. Conclusions: as strategies for coping with pain in children, there is adequate pharmacological and non-pharmacological treatment, in addition to nursing knowledge that prevents complications, as well as the education of children and family members about the disease, which favors improvement and adaptation to symptoms.